A multiwavelength study of nearby star-forming spiral galaxies and the clustering of star formation in M63. Issue 1 (11th August 2022) - Smith, Madison V; van Zee, L; Dale, D A; Staudaher, S; Wrock, T
ABSTRACT: This multiwavelength study of the star formation and star formation history (SFH) trends in the nearby universe looks at nine nearby late-type spirals. Spectral energy distributions fitted with measurements from the far-ultraviolet (FUV) to the mid-infrared are used to estimate parameters in a double-exponential SFH. Azimuthally averaged radial trends in the SFHs are shown and discussed for each galaxy. In addition to the radial analysis, catalogues of UV-selected sources are identified for each galaxy. An analysis of the clustering of the UV sources in M63 (NGC 5055) is done using a two-point correlation function. There is evidence for hierarchical star formation and clustering out to scales of several kpc. We then discuss the level of clustering in M63's sources with differing FUV − NUV colours, and how spiral arms may play a role in the organization of star formation even in the low surface brightness regions of a galaxy.